Ways of increasing the efficiency of photovoltaic transducers - Nikulcha, M. (My University, 2020)
The purpose of our research is to study the factors that reduce the efficiency of the PVT and the prospects for the introduction of innovative technologies to improve their energy efficiency.
Keywords: innovative technologies; energy potential; photovoltaic transducers